The Relationship Between Public and Private Sector Wages in Alberta - Swimmer, Gene; Williams, C. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1975)
The purpose of this study is to determine the nature and magnitude of any relationship between wage and salary changes in specified occupational classifications within the Alberta Civil Service and wage and salary changes in similar occupational classes in Alberta industry. In particular, the possibility of the « leader » role that public service wage and salary changes may play in the determination of occupational wage and salaries in other employment sectors within the Province of Alberta will be articulated.